Variations in the lipid composition of alfalfa roots during colonization with the arbuscular mycorrhizal fungus Glomus versiforme - Gaspar, María Laura (1997)
Lipids and their fatty acids were characterized and quantified during the development of the arbuscular mycorrhizal fungus Glomus versiforme in roots of alfalfa (Medicago sativa). A net increase in root total lipids was observed and was proportional to the development of arbuscular mycorrhizal fungus colonization. Triacylglycerols were the main lipid class in colonized roots and appear to have been synthesized by fungi. The increase of palmitoleic acid (characteristic of triacylglycerols from arbuscular mycorrhizal fungus) in roots colonized with G. versiforme reinforced this suggestion. Phosphatidylethanolamine and to a minor extent phosphatidylcholine also increased during the endophyte growth. Variations in the lipid classes of external mycelia isolated from one-, two- and three-mo old colonized roots with G. versiforme were also analyzed. Despite the continuous increase of triacylglycerols and phosphatidylethanolamine observed, the polar lipid class predominated in the external mycelia isolated from one- -mo old colonized roots and the neutral lipid class prevailed in the external mycelia obtained from three-mo old mycorrhizal roots. Biosynthesis of triacylglycerols in intra- and extramatrical mycelia as well as an induced synthesis of polar lipids in roots are suggested as the consequence of fungi colonization.